2010
DOI: 10.1103/physrevb.81.144109
|View full text |Cite
|
Sign up to set email alerts
|

Point defect distribution in high-mobility conductiveSrTiO3crystals

Abstract: We have carried out positron-annihilation spectroscopy to characterize the spatial distribution and the nature of vacancy defects in insulating as-received as well as in reduced SrTiO 3 substrates exhibiting high-mobility conduction. The substrates were reduced either by ion etching the substrate surfaces or by doping with vacancies during thin-film deposition at low pressure and high temperature. We show that Ti vacancies are native defects homogeneously distributed in as-received substrates. In contrast, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…To identify the defects responsible for PPC, positron lifetime measurements were carried out on as-received and annealed samples before and after illumination. Positron lifetime spectroscopy has been used to characterize vacancy defects in SrTiO 3 [19][20][21]34] as well as in other oxide materials such as ZnO [35,36]. In the present study, measurements were performed using a conventional fast-fast time coincidence spectrometer [37] with two BaF 2 -ray detectors mounted on photomultiplier tubes in collinear geometry, with an estimated time resolution of $200 ps.…”
mentioning
confidence: 99%
“…To identify the defects responsible for PPC, positron lifetime measurements were carried out on as-received and annealed samples before and after illumination. Positron lifetime spectroscopy has been used to characterize vacancy defects in SrTiO 3 [19][20][21]34] as well as in other oxide materials such as ZnO [35,36]. In the present study, measurements were performed using a conventional fast-fast time coincidence spectrometer [37] with two BaF 2 -ray detectors mounted on photomultiplier tubes in collinear geometry, with an estimated time resolution of $200 ps.…”
mentioning
confidence: 99%
“…Effect of n-type doping for T bomb = 135 s is weakened compared with that for T bomb = 45 s (not shown). This can be the result of the increase of titanium vacancies and the clustering of oxygen vacancies [13], [14]. Carriers are potentially scattered more by increasing defects as the result of longer bombardment, which slow the mobility.…”
Section: Resultsmentioning
confidence: 98%
“…Many computational studies reported in the literature are focused on defects that affect electrical properties (Mackie et al 2009), especially vacancy defects (Gentils et al 2010;Keeble et al 2010). In the work reported here, changes in properties such as conductivity are not of immediate interest.…”
Section: Materials Modelmentioning
confidence: 99%